Preparation and Evaluation of Rebamipide Film using Casting Technique for Local Action - Radhi, Zainab Abdulmohsin Hadi; Ghareeb, Mowafaq Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2019)
AbstractThe aim of this study was to prepare rebamipide ocular inserts in order to extend its release on the ocular surface for dry eye treatment. Solubility study was applied to the drug with or without l-arginine using different solvents. Solvent casting technique was used to prepare the inserts; l-arginine was used to solubilize the drug, hydroxypropyl methylcellulose grades (E5 and K15M) and poly ethylene glycol 200 were used as excipients. The inserts were evaluated for their physical and mechanical properties, moisture loss% and absorption %, surface pH, and in-vitro drug release. The use l-arginine exhibited an enhancement of rebamipide solubility in both deionized water and phosphate buffer (pH 7.4) by approximately 250 times and 3 times, respectively. The formulations showed uniform weight and thickness except for F1, and all showed uniform drug content. The absence of plasticizer in F1 caused haziness in its appearance and brittleness of the inserts. F3 which contain hydroxypropyl methylcellulose K15M showed good physical and mechanical properties thus was selected for in vitro release and was compared to the marketed brand Mucosta® suspension eye drop; F3 showed significant enhancement in extending the release of rebamipide compared to the reference marketed brand.Keywords: Rebamipide, L-arginine, Ocular insert, Solvent casting technique ??????? ????? ?? ??? ??????? ?? ????? ?????????? ?????? ???? ???? ????? ??????????? ??? ??? ????? ????? ????? ?????. ??? ????? ??????? ?????? ????? ???????? ? ???? ????? ???????? ?????? ??????. ??????? ????? ??????? ? ???? ?????? ??????? ? ?????? ???????? ?????? ?????? ? ?? ??????? ??????????? ?????? ???? ???????? ?????? (K15M ? E5 ) ? ?????? ?????? ??????? ?????. ?? ????? ?????? ?????????? ? ?????????? ??????? ? ???? ?????? ??????? ??????? ????? ? ?????? ??????? ? ???? ???? ??????????? ???? ??????? ????? ????? ????? ?????? ?? ???????. ????? ??????? ?? ???????? ???? ??? ????? ??????? ???????????? ?? ?? ?? ????? ??????? ???????? ? ????? ???????? ?????? (?? ??????????? 7.4 ), ?????? ????? 250 ??? ? ???? ???? ??? ???????. ???????? ????? ??? ? ????? ??????? ???? ??? (F1 ) ? ?? ???????????? ????? ????? ?????? ????????. ??? ???? ???? ??(F1 ) ??? ??? ?????? ??????? ? ??????. ( F3) ???? ????? ??? ??????????? ?????? ???? ?????????? (M 15 K) ???? ???? ???????? ? ????????? ???? ? ??? ?? ??????? ?????? ??????? ?????? ?????? ?? ??????? ? ??????? ??????? ?????? ? ?? ????? ????? ????? ?????? ???? (????????) ? ?? ???? ?? ??????? F3 ???? ????? ???? ?? ????? ????? ???????????? ?????? ??????? ?????? ?????? ?????. ??????? ?????????: ??????????, ????????, ??????? ??????, ????? ??????? ? ????